2005
DOI: 10.1128/jcm.43.9.4407-4412.2005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance and Epidemiologic Analyses of Mycobacterium avium and Mycobacterium intracellulare among Patients without AIDS

Abstract: The clinical significance and prevalence of Mycobacterium avium and Mycobacterium intracellulare were analyzed in a cohort of 7,472 patients who, from 1999 to 2003, sought care at the University of Texas M.D. Anderson Cancer Center, Houston, and had cultures performed for mycobacteria. Patients were stratified for age, sex, and underlying diseases, and bacteria were identified by 16S rRNA gene sequencing. M. avium was isolated in 62 (0.83%) of 7,472 patients and M. intracellulare in 65 (0.87%). Clinically, onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
61
3
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 22 publications
(26 reference statements)
5
61
3
2
Order By: Relevance
“…(3,19), is better able to invade and replicate inside macrophages than M. intracellulare (14), and has been associated with more invasive forms of MAC disease (3,10,21,27). Our data differ from the findings of a recent study by Han et al, who found that M. avium (identified by 16S rRNA sequencing) isolated from clinical specimens was actually less likely to be associated with pulmonary disease than was M. intracellulare (9). In that study, M. avium isolation was strongly associated with hematologic malignancy but did not often cause clinical disease (16.1% of isolates), while 63.1% of patients with M. intracellulare had clinical disease.…”
contrasting
confidence: 57%
“…(3,19), is better able to invade and replicate inside macrophages than M. intracellulare (14), and has been associated with more invasive forms of MAC disease (3,10,21,27). Our data differ from the findings of a recent study by Han et al, who found that M. avium (identified by 16S rRNA sequencing) isolated from clinical specimens was actually less likely to be associated with pulmonary disease than was M. intracellulare (9). In that study, M. avium isolation was strongly associated with hematologic malignancy but did not often cause clinical disease (16.1% of isolates), while 63.1% of patients with M. intracellulare had clinical disease.…”
contrasting
confidence: 57%
“…For example, within the MAC, M. intracellulare is more pathogenic than M. avium and some strains demonstrate hypervirulence leading to progressive lung disease and poor prognosis [36][37][38]. Many NTM infect humans via adherence to the respiratory mucosa.…”
Section: Virulence Factorsmentioning
confidence: 99%
“…In our earlier study (34), we noted that the frequent isolation of M. avium from patients with cancer was mainly due to the use of more diagnostic bronchoscopy procedures instead of being due to true infections. In fact, only 16.2% of all 62 patients with M. avium isolation showed evidence of definite or probable infection in that study whereas 63.1% of 65 patients with M. intracellulare exhibited such evidence of infection.…”
Section: Discussionmentioning
confidence: 99%
“…The isolation sources of the M. avium strains were categorized as tissue, respiratory tract, abdominal source, and others. The clinical significances were categorized as definitive, probable, or possible infection or contaminant based on the American Thoracic Society criteria (35) and our previous experience (34). Objective criteria, such as sterile specimens, radiographic abnormalities, and multiple isolations, were emphasized.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation